Bridging Satisfaction to Loyalty: The Role of Service Quality and Customer Stickiness in Indonesia's Online Food Delivery Industry - Putra, Agus Triana; Cahyadi, Yayan; Permana, Dimas; Mariani, Minsani (Program MM Universitas Surabaya, 2025)
Purpose: This study examines the influence of service quality dimensions which are tangibles, reliability, responsiveness, empathy, and assurance on customer satisfaction and their subsequent impact on customer loyalty in the context of online food delivery (OFD) services in Indonesia. Additionally, it explores the mediating role of customer stickiness in the relationship between customer satisfaction and loyalty. Method: The study employs a quantitative-explanatory research approach with a sample of 325 respondents, selected using purposive sampling. Data were collected through an online questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). Result: The findings reveal that tangibles and reliability are dominant factors influencing customer satisfaction. Customer satisfaction significantly enhances customer loyalty, primarily through the mediating role of customer stickiness. The SERVQUAL model was validated in the OFD context, highlighting the importance of improving service quality to foster customer satisfaction and loyalty.